اجتاهات استخدام الدعاة األردنيني لإلعالم اإلجتماعي وعالقته مبواجهة خطاب الكراهية - Ahmad Mohammad Ahmad Alnadi; Ehab Ahmed Awais (Malaysian Institute of Science and Development (MISD), 2024)
This study aimed to identify the trends of Jordanian Islamic preachers using social media and its relationship to confronting hate speech, the researcher used the descriptive approach in both its descriptive and analytical aspects. The study was conducted in the context of a sample survey of Islamic Jordanian preachers' publications on Facebook.The researcher used the content analysis tool on a sample of preachers who were represented by six preachers such as Dr. Ahmed Nofal, Muhammad Al-Qudah, Dr. Zaid Al-Masry, Dr. Amjad Quresha, Dr. Iyad Qunaibi, and Dr. Hamza Al-Majali. The study concluded that the nature of publications of Jordanian preachers is religious in general, and the Jordanian preachers' posts on Facebook do not feed hate speech generally, except a limited and narrow scope, and that there are high similarities between preachers in their way for Da'wah